An observational study of postoperative handoff standardization failures. (July 2021) - Abraham, Joanna; Meng, Alicia; Sona, Carrie; Wildes, Troy; Avidan, Michael; Kannampallil, Thomas
Highlights: Little is known about the challenges to handoff standardization attempts. The SEIPS model helps to identify challenges and compliance failure root contributors across handoff work system elements. Flexibly standardized OR-ICU interventions may mitigate compliance failures and sustainability issues. Handoff bundled interventions supporting all handoff phases can potentially improve process and clinical outcomes. Telemedicine can improve handoff resilience and support a "fresh-eye perspective" in care planning and decision making. Abstract: Background: Patient handoffs from an operating room (OR) to an intensive care unit (ICU) require precise coordination among surgical, anesthesia, and critical care teams. Although several standardized handoff strategies have been developed, their sustainability remains is poor. Little is known regarding factors that impede handoff standardization. Purpose: Our objectives are three-fold: (1) highlight compliance failures with standardized handoffs; (2) identify factors contributing to compliance failures; and (3) develop guidelines for sustainable handoff interventions and processes. Methods: We used ethnographic data collection methods—general observations, handoff shadowing, and semi-structured clinician interviews—with 84 participants from OR, ICU, and telemedicine teams at a large academic medical center. We conducted thematic analysis supported by inductive and deductive coding using the Systems Engineering Initiative for Patient Safety (SEIPS) framework. Results: Post-operative handoffs can be characterized into four phases: pre-transfer preparation, transfer and setup, report preparation and delivery, and post-transfer care. We identified compliance failures with standardized handoff protocols and associated risk factors within the OR-ICU work system including limited teamwork, absence of handoff-specific tools, and poor clinician buy-in. To improve handoffs, clinicians provided suggestions for developing collaborative Electronic Health Record (EHR)-integrated handoff tools and re-engineering the handoff process. Conclusions: Compliance failures are prevalent in all handoff phases, leading to poor adherence with standardization. We propose theoretically grounded guidelines for designing "flexibly standardized" bundled handoff interventions for ensuring care continuity in OR to ICU transitions of care.